Expression and purification of the non-tagged LipL32 of pathogenic Leptospira - P. Hauk (Brazilian Journal of Medical and Biological Research, 2011)
Leptospirosis is a reemerging infectious disease and the most disseminated zoonosis worldwide. A leptospiral surface protein, LipL32, only occurs in pathogenic Leptospira, and is the most abundant protein on the bacterial surface, being described as an important factor in host immunogenic response and also in bacterial infection. We describe here an alternative and simple purification protocol for non-tagged recombinant LipL32. The recombinant LipL32(21-272) was expressed in Escherichia coli without His-tag or any other tag used to facilitate recombinant protein purification. The recombinant protein was expressed in the soluble form, and the purification was based on ion exchange (anionic and cationic) and hydrophobic interactions. The final purification yielded 3 mg soluble LipL32(21-272) per liter of the induced culture. Antiserum produced against the recombinant protein was effective to detect native LipL32 from cell extracts of several Leptospira serovars. The purified recombinant LipL32(21-272) produced by this protocol can be used for structural, biochemical and functional studies and avoids the risk of possible interactions and interferences of the tags commonly used as well as the time consuming and almost always inefficient methods to cleave these tags when a tag-free LipL32 is needed. Non-tagged LipL32 may represent an alternative antigen for biochemical studies, for serodiagnosis and for the development of a vaccine against leptospirosis.